Mass spectrometric analyses of cell and tissue glycomes - Haslam,SM; Pang,PC; Antonopoulos,A; Dell,A (2015)
This chapter discusses mass spectrometric (MS) strategies for mammalian cell and tissue glycomics and places the principles underlying them within a historical framework. Ultrahigh-sensitivity MALDI-TOF/TOF glycomic methodologies are based on the analysis of permethylated derivatives of pools of glycans that are released from glycoproteins or glycolipids enzymatically or chemically. Very complex mixtures from biological extracts of cells and tissues can be screened in this way, thereby revealing the types of glycans present and, importantly, providing clues to structures that are likely to be functionally important. Optimal glycomic workflows are illustrated by glycomic data from human cytolytic T lymphocytes. Fragmentation pathways that are central to glycomics are briefly outlined, and the use of the Glyco Work Bench tool to assist fragment ion annotation is briefly explained. Finally, the open-access data repositories of the Consortium for Functional Glycomics, which contain glycomics data for murine and human hematopoietic cell populations, are described.